Implementasi Normalized Euclidean Distance Dalam Pengenalan Wajah Pada Sistem Absen - Virra Trisvie Andini (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
The need for employees to be absent is one of the important things, especially for those who work in a company, this makes the company need a system to perform attendance. Euclidean Distance which is normalized in facial recognition on absentee systems running in the industrial sector is still conventional, where attendance management still uses a notebook, so we need a system that can assist in managing attendance data in the industrial sector. The attendance system on facial recognition aims to assist in the management of attendance data for employees and companies such as employee data, attendance data, outgoing attendance reports, and incoming attendance. The system is built based on android and WEB with the programming language Android studio and MySQL